IMF Staff papers : Volume 35 No. 2. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1988)
It has been argued that 'buy-backs' and 'debt-equity swaps' allow developing countries to benefit from market discounts on their external debt. It is argued here, however, that if such programs are expected to be successful in increasing the market value of remaining debt, they also lead to a roughly equivalent increase in prices at which a buy-back or debt-equity swap could be carried out.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet